Binding of Heparin to Human Leukocytes - Harenberg, J.; Malsch, R.; Piazolo, L.; Heene, D. L. (Hämostaseologie, 1994)
Non-anticoagulant actions of heparins and related sulfated polysaccharides in thrombosis, atherosclerosis and inflammation are currently under investigation. To analyze the involvement of leukocytes in this mechanism, a fluorescein labeled low molecular mass heparin-tyramine has been prepared (LMMH-tyr-Fitc) to investigate the binding of heparin and other sulfated polysaccharides to granulocytes, monocytes, and lymphocytes. The fluorescence intensity on leukocytes was quantified using flow cytometry as detection method. LMMH-tyr-Fitc bound dose-dependently to all three leukocyte populations. Phycoerythrin-labeled CD-antibodies identified the specificity of the binding of LMMH-tyr-Fitc to lymphocytes, monocytes, and granulocytes. Unfractionated heparin and LMM-heparin displaced LMMH-tyr-Fitc dose-dependently from granulocytes, monocytes, and lymphocytes and were more effective compared with dextransulfate. Heparin, LMM-heparin and LMMH-tyr-Fitc bound to leukocytes inhibited factors Xa activity in the S2222 chromogenic substrate assay. The data indicate that negatively charged polysaccharides bind to the surface of granulocytes, monocytes and lymphocytes and that binding is in part depending on the number of negatively charged groups of glycosaminoglycans. After binding to the surface of leukocytes heparin exerts still anticoagulant activity indicating its intact biological function. The binding of heparins to leukocytes may significantly contribute to the antithrombotic and to other biological activities.
Keywords: Glycosaminoglycans; heparin; low molecular mass heparin-tyramine; leukocytes